Unemployment and Innovated Problems of Iraqi Youth Analytical-Field Study of Drugs - Abd Jabr Al-Khafaji, Waleed (International Journal of Psychosocial Rehabilitation, 2020)
Youth as a social group is a basic partner and the main element in the development process. There is an increased realization of youth problems at various levels of decision-making in Iraq. Their empowerment and inclusion projects in the development process have always clashed with obstacles of violence and political and social instability. That necessarily leads to fragmenting this group, and some of them became a part of the conflict mechanisms in society. The present study aims to examine the negative causes and effects that contribute to the spread of the problem of drug use, including unemployment, on society in general and the youth category in particular. The applied side of the study will focus on trying to know the dimensions of the problem through the study sample to develop appropriate proposals that limit or reduce its negative effects on individuals in society. The significance of the study is embodied, in fact, with the importance and graveness of the phenomenon that it deals with because of its serious repercussions on the individual, family, and society. As for the study methodology, it relies on the descriptive analytical approach and the social survey one to capture aspects of the phenomenon being studied. The field side consists of an intentional sample of individuals who used drugs of various ages who went to cafes in the city of Baghdad, with a volume of 65 users. A number of conclusions and proposals are reached as ways to treat the studied phenomenon.